2013
DOI: 10.1007/s10903-013-9953-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Illness, and the Social Environment: Depressive Symptoms Among First Generation Mandarin Speaking Chinese in Greater Los Angeles

Abstract: Purpose This study documents the indirect effects of social and environmental variables as mediated by immigrant stress and physical health. Methods Using data from a large dual frame sample of first generation mandarin speaking Chinese immigrants in metropolitan Los Angeles counties with the largest groups of Chinese immigrants, this study uses a path analytic approach to trace how predictors are related to depressive symptoms and to measure direct and indirect influences of variables. Results Although bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Working mothers may have a higher level of depressive symptoms in their first month of returning to work. Family income insufficiency causes great stress, which increases postpartum depressive symptoms [26]. Similar associations have been reported in previous studies [27,28].…”
Section: Discussionsupporting
confidence: 86%
“…Working mothers may have a higher level of depressive symptoms in their first month of returning to work. Family income insufficiency causes great stress, which increases postpartum depressive symptoms [26]. Similar associations have been reported in previous studies [27,28].…”
Section: Discussionsupporting
confidence: 86%
“…Many health studies in migrants and ethnic minorities have adopted purposeful sampling methods to recruit participants in specific premises including clinics, churches, and community centers [ 7 , 8 ]. In some studies, participants were recruited through a telephone directory by selecting surnames which might indicate the person’s ethnic background [ 9 , 10 ]. Nevertheless Smith et al proposed that a telephone directory sampling strategy was less likely to include subjects born outside of Australia than a door-to-door population census [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that 85% of participants in the postal survey had been residing in Australia for more than 5 years compared with about half of participants in the Web-based survey. Similarly, studies amongst US migrants found samples of longer-stay migrants using a telephone directory list (151). Due to the immigration regulations, new arrival migrants are generally young and well educated.…”
Section: Principle Findingsmentioning
confidence: 99%
“…Even so, however, that potential change in demographics is unlikely to account for the observed differences between two surveys. A recent study in the United States, using a telephone directory to obtain a sample of Chinese migrants also showed that the sample population of a postal survey was relatively older and they were longer-stay migrants (151).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation